Alternatif Model Penerapan Perencanaan Strategis Dalam Penataan Ruang Kota di Indonesia - Djunaedi, Achmad (Journal of Regional and City Planning, 2001)
The application of strategic planning style for regional development planning that has been started in Indonesia arises a question: can the style also be applied for urban spatial planning? Some literatures have provided theoretical concepts. in addition, some urban cases in the world have concluded two models of urban spatial strategic planning:  spatial plan goes hand-in- hand cohesively with the regional development strategic plan, and (2) regional development plan acts as umbrella for all other plans including spatial plan. Based on the assessment on these two models, two alternative models for the application of strategic planning for urban spatial planning in Indonesia are proposed.